(untitled) (Research, Society and Development, 2022)
Objective: To analyze the incidents of AIDS mortality among adolescents in the state of Paraná. Method: A descriptive, time-series study, based on secondary data regarding AIDS-related deaths among adolescents aged 10 to 19 years, in the state of Paraná. Results: High death rates were identified among young people aged 15 to 19 years, especially in the years 2013, 2014 and 2017. The notifications of cases that evolved to death are mainly related to female adolescents, white and aged 8 to 11 years of study. Although the results found, it is highlighted that due to the social stigma, in the recognition of the severity of the disease, and in the difficulties of access to health services and, consequently, in the early detection, it is possible that there is underreporting of cases and deaths resulting from the disease. AIDS. Conclusion: As it is a chronic and permanent infection in most cases, it is necessary to know the statistics of the disease to determine the preventive measures that can be adopted, as well as to investigate the future consequences on the quality of life of these adolescents.